Antibacterial effect of copper composites against Xanthomonas euvesicatoria. (January 2021) - Fan, Qiurong; Liao, Ying-Yu; Kunwar, Sanju; Da Silva, Susannah; Young, Mikaeel; Santra, Swadeshmukul; Minsavage, Gerald V.; Freeman, Joshua H.; Jones, Jeffrey B.; Paret, Mathews L.
Abstract: Bacterial spot disease caused by Xanthomonas euvesicatoria is one of the major constraints for pepper production in Florida and worldwide. The common prevalence of copper (Cu)-tolerant X. euvesicatoria strains has reduced the efficacy of Cu based bactericides against bacterial spot of pepper. In this study, we evaluated antimicrobial activity of three Cu-based nanocomposites, namely, core-shell Cu (CS–Cu), fixed-quat Cu (FQ-Cu) and mixed-valence Cu (MV-Cu), along with Kocide® 3000, which is a micron size metallic Cu bactericide and is commercially available, both in vitro and in greenhouse trials, against a Cu-tolerant strain of X. euvesicatoria . In repeated in vitro tests, X. euvesicatoria growth was completely inhibited 24 h after exposure of bacterial cells to 500 and 1000 μg/ml of MV-Cu and all concentrations of FQ-Cu and CS-Cu (100, 200, 500, and 1000 μg/ml) treated for 1 h. Micron size copper, even at 1000 μg/ml, had no statistical difference in growth in comparison to the untreated control (P = 0.05; LSD). In the repeated greenhouse experiments, plants treated with all the copper composites exhibited less bacterial spot severity than untreated control and similar or significantly less than Cu-mancozeb (P < 0.05). However, MV-Cu was the only Cu composite with no phytotoxicity on plants under controlled conditions. This study shows potential to use Cu-based nanoparticles for efficient management of bacterial spot on pepper.